Triple photon production at the Tevatron in technicolor models - Zerwekh, A.; Dib, C.; Rosenfeld, Rogério [UNESP] (Elsevier B.V., 2002)
We study the process p (p) over bar --> gammagammagamma as a signal for associated photon-technipion production at the Tevatron. This is a clean signature with relatively low background. Resonant and non-resonant contributions are included and we show that technicolor models can be effectively probed in this mode. (C) 2002 Elsevier B.V. B.V. All rights reserved.